Zur Neolithisierung des Mittleren Niltals und angrenzender Regionen : kultureller Wandel vom Mesolithikum zum Neolithikum im Nord- und Zentralsudan - Dittrich, Annett, (BAR International Series ;, 2011)
"A study of cultural change and development from the Mesolithic to the Neolithic in the north and central Sudan."-- Publisher's website